Genome sequencing and pathogenicity of recent infectious bursal disease viruses in Malaysia - Bako, Aliyu Hayatuddeen (2021)
Infectious bursal disease virus (IBDV) is an immunosuppressive viral pathogen that causes infectious bursal disease (IBD) in susceptible young chickens worldwide. Vaccination is a critical component in controlling IBD. The IBDV has a high genetic mutation rate which may result in antigenic variant. Antigenic variants have been reported from several laboratories including countries in Asia. The last characterisation of Malaysian IBDV full genome was in the year 2008. However, there is paucity of information on the recent characterisation and pathogenicity of IBDV isolated from commercial flocks in Malaysia. The present study focused on the genome-wide analysis of recently isolated IBDV in Malaysia using NGS technology, and the pathogenicity of the characterised strains were evaluated in specific pathogen-free (SPF) and immunised SPF chickens. Thirty bursal samples were used for the study, where 25 samples were collected from tentatively IBD diagnosed flocks in a commercial vaccinated broiler farm, and 5 samples were earlier submitted to the laboratory of vaccine and biomolecules, IBS. Eleven positive IBDV isolates were investigated. The isolates were detected using reverse transcription-polymerase chain reaction (RT-PCR) targeting the hypervariable region (HVR) of the VP2 gene. The nucleotide and amino acid (aa) sequences were compared with the previously characterised IBDV strains. Based on the VP2 sequences, five IBDV isolate were selected for whole-genome sequencing using the MiSeq platform. Pathogenicity of UPM1056/2018 (vvIBDV) and UPM1432/2019 (vaIBDV) strains was evaluated in 4-week-old (SPF) chickens. The chickens were randomly divided into 3 groups; group 1 (control), groups 2 and 3 birds were challenged with the vaIBDV and vvIBDV, respectively. Three birds from each group were weighed, euthanised and necropsied at 2, 3, 4, 5, 7 and 21 dpc. Pathological lesions were evaluated, and viral load in the tissues and cloacal shedding were determined. Immune-complex classical vaccine (vaccine A) and attenuated live very virulent vaccine (vaccine B) were used for immune-protection experiments in SPF chickens. One-day-old (n=75) SPF chickens were randomly divided into 3 groups of 25 chicks each. Group 1 (control), group 2 (Vaccine A) and group 3 (Vaccine B). Variant IBDV, UPM1432/2019 was used for the challenge at 21- and 28- days post vaccinations (dpv). Five birds from unchallenged and challenged groups were sacrificed at 7 dpc, and blood, bursa, spleen, and cloacal swabs were collected. Antibodies (Ab), lymphoid lesions and viral load were determined. Deduced aa sequences of HVR revealed the characteristic motifs that showed seven isolates belong to very virulent strains (genogroup 3), two isolates belong to variant strains (genogroup 2), and two have an identity to vaccine strain (genogroup 1) of IBD viruses. The serine rich-heptapeptide sequence “SWSASGS” was conserved in all 11 isolates. Also, the complete genome sequences revealed the presence of aa substitutions; 12 in VP5, 15 in VP2, 5 in VP4, 4 in VP3 and 10 in VP1 for vaIBDV, UPM1432/2019 strain. UPM1056/2018 strain showed highest aa substitutions among the vvIBDV strains with aa substitutions; 2 in VP5, 8 in VP2, 4 in VP4, 5 in VP3 and 2 in VP1. Unlike the other vvIBDV characterised in this study, UPM766/2018 lacks the MLSL aa residues in VP5, whilst IBS536/2017 has 154 aa. The aa tripeptides: 145/146/147 (TDN) of VP1 were conserved for the vvIBDV, while NED was observed for the variant IBDV. The phylogenetic analysis showed that the isolates formed clustered with the respective genogroups. The vaIBDV clustered with the American and Chinese variant viruses and highly comparable to the Chinese novel variants with 99.9 % identity. While the vvIBDV grouped with the vvIBDV of other countries, but they are closely related to the previously characterised Malaysian vvIBDV. Unlike UPM1056/2018 group, birds from UPM1432/2019 group did not show clinical signs or death. Both strains induced pathological lesions on the BF in the infected chickens with a more severe lesion in UPM1056/2018 group. The bursal body index (BBIX) for UPM1432/2019- and UPM1056/2018 groups was < 0.7 from 2 dpc and continued to decrease to 0.49 and 0.45, respectively at 21 dpc. UPM1432/2019 strain was detected for longer duration in the bursa than UPM1056/2018 strain. The variant strain, UPM1432/2019, induced bursal damage in immunised chickens in the presence of antibodies titres at two different age groups, 28- and 35- dpv (7 dpc). The BBW of vaccinated unchallenged groups did not differ significantly (P > 0.05) from that of the vaccinated challenged groups. But the mean BBW for the unchallenged control group was higher (P < 0.0001) than for the control challenged group. Microscopically, the bursae of the challenged groups showed significant atrophy, particularly in the control group. The bursal lesion score was higher (P > 0.05) in control and vaccine B challenged groups than that in vaccine A challenged group of the two-challenge periods. Also, the viral loads were significantly higher (P < 0.01) in the bursa than in the spleen, and the highest (P < 0.05) viral load was found in control challenged group than the vaccinated ones. The study has reported IBDV variant for the first time in Malaysia, and the majority of IBDV circulating in Malaysia are evolving very virulent strain. Both the vaIBDV and vvIBDV induced similar pathological lesions in SPF chicks. The two vaccines could not adequately protect against the Malaysian vaIBDV challenge. Our findings explained the urgent need for the development of new vaccines against the vaIBDV. Further research is required to assess the potentiality of vaccine development from the variant strain.